Validity of Plate Diagrams for Estimation of Energy and Protein Intake of Nursing Home Residents Receiving Texture-Modified Diet: An enable Study - Ott, Angela; Voigt, Maria; Sieber, Cornel; Volkert, Dorothee (Journal of the American Medical Directors Association, 2020)
Objectives: Nursing home (NH) residents receiving texture-modified diet (TMD) are at risk of inadequate nutritional intake and subsequent malnutrition. It is essential to monitor dietary intake to take corrective actions, if necessary. Plate diagrams (PDs) are widely used to assess dietary intake in institutions but little is known about their validity for TMD. Design: Dietary intake at main meals was assessed by nursing personnel via PDs and scientific personnel via weighing records (WRs). Setting and Participants: 17 NH residents receiving TMD on a regular basis. Methods: Intake from main meals (breakfast, lunch, and dinner) at 48 days was estimated by nursing personnel in quarters of the offered amount [nothing, ¼, ½, ¾, all, all plus second helping ([Formula presented]), or I do not know] and by scientific personnel via WRs. PD estimation was multiplied by the energy and protein content of the offered meal determined by WR and compared to WR intake results. Sums of daily PD quarters were drawn against WR intake results. Results: Energy and protein intake from main meals separately and in total per day were highly correlated (r > 0.854, all P <.001). Paired statistics showed no significant differences between assessment methods (P >.05). Mean differences [±standard deviation (SD)] between PD and WR were 13.9 (±68.6) kcal, which is 1.7% of the mean weighed caloric intake, and 0.2 (±3.3) g protein, which is 0.5% of the mean weighed protein intake per day. Daily energy and protein intake from main meals determined by WR varies widely within each category of summed daily intake quarters; for example, a sum of PD quarters of 12 (ie, “all eaten at all meals”) showed corresponding WR intake levels from 394.6 to 1368.9 kcal and 16.3 to 63.0 g protein. Conclusions and Implications: Energy and protein intake from TMD estimated by PD corresponds very well to WR-determined intake, if the energy and protein content of the offered meals is known.
CRIS-Team Scopus Importer:2020-02-04
Keywords: chewing and/or swallowing problems; enable-cluster; nursing home; plate diagram; texture-modified diet; weighing record